(untitled) (International Journal of Occupational Safety and Health, 2024)
Introduction: The use of personal protective measures holds relevance despite mass immunization coverage of COVID-19 vaccination in the population. This is because vaccination only gives protection from severe COVID-19 and does not prevent the risk of infection. Medical students can be vital in training people in infection control practices. The study aimed to assess the practices of undergraduate medical students regarding personal protective measures against COVID-19. Methods: A cross-sectional study was done among first to final-year students at a private medical college in Mangalore. Data were collected using a Microsoft form. Results: The mean age of the 302 participants was 21.2±1.6 years. The majority of them were females [179 (59.3%)]. Face mask was worn by 295(97.7%) participants. Non-recommended types of face masks like using cloth masks [108 (36.6%)] and handkerchiefs [7 (2.4%)] were reported by participants. 35 (11.9%) of them wore the face mask incorrectly. Periodicity of replacement of disposable type masks was not done every day by 181(61.4%) participants. 142(48.1%) of them did not dispose of masks whenever they became moist on every occasion. Only 79 (26.8%) always practiced proper disposal of face masks. Hand sanitizer to disinfect hands was always used by 102 (33.8%) participants. Only 42 (13.9%) participants practiced correct practice of hygiene hand wash always. Only 58 (19.2%) participants had a good level of practice. Practice level was significantly poorer among males and first-year students. Conclusion: Several gaps in preventive practices against COVID-19 were identified, particularly among males and first-year students. These issues need to be addressed among medical students in future training programs.